PERAN BUKU AJAR DALAM MENINGKATKAN PEMAHAMAN SISWA KELAS VII TERHADAP MATA PELAJARAN AKIDAH AKHLAK DI MTS NEGERI 1 BUTON - Imel Kapuani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using textbooks in improving students' understanding of the subject of Aqidah Akhlak in class VII I at MTs Negeri 1 Buton. The research method used is a quasi-experimental design with a pretest-posttest control group design. The research sample consists of two groups: the experimental group, which uses textbooks, and the control group, which does not use textbooks, each comprising 30 students. Data were collected through comprehension tests (pretest and posttest), classroom observations, and questionnaires to measure students' responses to the use of textbooks. The research results show that the average posttest scores of the experimental group increased significantly compared to the control group. The average pretest score of the experimental group was 62.4, while the posttest score reached 82.6, indicating an increase of 32.37 percent. Meanwhile, the control group, which did not use textbooks, only experienced an increase from 61.8 to 72.1, or 16.68 percent. The t-test results showed a t-statistic value of 28.1 and a p-value of 0.0, indicating a significant difference between the two groups. Additionally, classroom observations revealed that students who used textbooks were more active in discussions and demonstrated a better understanding of Aqidah Akhlak concepts.